Assessment of Soil-Structure Resonance Probability of Educational Buildings in Kageshwori Municipality - Chaulagain, Saroj; Bijukchhen, Subeg Man; Poudel, Youbraj (Journal of Science and Engineering, 2026)
This study focuses on assessing the possibility of soil–structure resonance in school buildings located within Kageshwori Manohara Municipality, Nepal, by comparing the natural time periods of the ground and the structures. Ambient vibration measurements were carried out using geophones to determine the predominant period of both the selected school buildings and the nearby free-field sites. The Nakamura Horizontal-to-Vertical Spectral Ratio (HVSR) technique was applied to ambient noise data to identify the predominant soil period, which was found to range between 1.14 and 3.23 seconds, reflecting the local ground response characteristics. Similarly, the natural periods of the buildings, obtained through the Floor Spectral Ratio (FSR) or Horizontal-to-Horizontal (H/H) method, ranged from 0.11 to 0.37 seconds. Since the soil and building periods do not coincide, the likelihood of resonance occurring in these school structures is quite low. However, the seismic vulnerability index values of the ground beneath the studied buildings fall between 44.96 and 282.61 (classified as Very High), suggesting that the area is composed of relatively soft ground with thin sediment layers. Furthermore, the results show that buildings tend to be more vulnerable in the east–west (EW) direction than in the north–south (NS) direction, highlighting the need for targeted retrofitting measures. Overall, this study provides important insights for engineers and decision-makers aiming to enhance the seismic resilience of educational buildings in this earthquake-prone municipality.